1994
DOI: 10.1016/0014-5793(94)00932-5
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the existence of a third family among peptidyl‐prolyl cis/trans isomerases Amino acid sequence and recombinant production of parvulin

Abstract: In addition to the major cyclophilin-like peptidyl-prolyl cisltrans isomerases (PPIases) of Escherichia coli an enzyme of very low relative molecular mass (10.1 kDa) was discovered in this organism which gave first indication of the existence of a novel family in this enzyme class [1994, FEBS Lett. 343, 65-691. In the present report we describe the chemically determined amino acid sequence of four peptides derived from the IO. 1 kDa protein by the treatment with either cyanogen bromide or endoproteinase Lys-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
167
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 26 publications
0
167
0
4
Order By: Relevance
“…In addition to the cyclophilins, two other families of PPIs have been described, the FK506-binding proteins (FKBPs) (Harding et al, 1989;Siekierka et al, 1989) and parvulins (Rahfeld et al, 1994), both structurally unrelated to the cyclophilins. In spite of this, it has been shown that overexpression of cyclophilin A can rescue a lethal parvulin mutant in yeast (ArevaloRodriguez et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cyclophilins, two other families of PPIs have been described, the FK506-binding proteins (FKBPs) (Harding et al, 1989;Siekierka et al, 1989) and parvulins (Rahfeld et al, 1994), both structurally unrelated to the cyclophilins. In spite of this, it has been shown that overexpression of cyclophilin A can rescue a lethal parvulin mutant in yeast (ArevaloRodriguez et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A parvulin protein was originally found in Escherichia coli as a novel PPIase that consists of only 92 amino acids and is hence named parvulin (Latin: parvulus, very small; Rahfeld et al, 1994). Later on, parvulin homologs were found in both prokaryotic and eukaryotic organisms like SurA from E. coli (Eisenstark et al, 1992), Ess1/Ptf1 from yeast (Saccharomyces cerevisiae; Hanes et al, 1989;Hani et al, 1995), and Pin1 from human (Lu et al, 1996).…”
mentioning
confidence: 99%
“…We have previously identified in Bacillus subtilis a membrane-bound lipoprotein, PrsA, which according to sequence similarity belongs to the parvulin family of PPIases (18). In PrsA a stretch of 90 amino acids is 45% identical with E. coli parvulin.…”
mentioning
confidence: 99%